Dietary index for gut microbiota and its protective role against kidney stones: evidence of diabetes as a mediator from NHANES cross-sectional data - Wang, Lei; Wu, Junjun; Jiang, Ziwen; Wang, Chao; Lin, Fuxiang; Zhong, Yuxiang; Zhao, Pengpeng; Wei, Wei; Huang, Jianhua; Xu, Zhanping (Frontiers in Nutrition, 2025)
BackgroundThe dietary index for gut microbiota (DI-GM) reflects dietary patterns that support gut microbial health and may influence kidney stone (KS) risk. The role of DI-GM and its mediation by diabetes in KS pathogenesis remains unclear.ObjectiveTo investigate the association between DI-GM and KS prevalence, assess the mediation effect of diabetes, and explore subgroup-specific effects and underlying mechanisms.MethodsA cross-sectional analysis of NHANES (2007–2018) data was conducted using a stratified, multistage probability sampling design. A total of 19,841 participants were included in the final analysis. Data entry and statistical analysis were performed using Empower version 4.2 (X&Y Solutions, Inc., Boston, MA, United States) and R version 3.4.3 (R Foundation). Multivariable logistic regression was employed to assess the association between DI-GM and KS prevalence, with statistical significance set at p < 0.05. Mediation analysis evaluated diabetes’s contribution to this relationship, and subgroup analyses were conducted based on sex, race/ethnicity, and alcohol consumption.ResultsHigher DI-GM scores were associated with lower KS prevalence (adjusted OR: 0.78, 95% CI: 0.65–0.92 per SD increase). Diabetes mediated 9.27% of this relationship. Subgroup analyses revealed stronger protective effects among females, non-Hispanic Black individuals, and heavy drinkers. Mechanistically, DI-GM may reduce KS risk through gut microbial modulation of oxalate metabolism, urinary citrate excretion, and systemic inflammation.Conclusion and recommendationsHigher DI-GM scores are associated with reduced KS prevalence, partially mediated by diabetes. These findings highlight the role of dietary interventions targeting gut microbiota in KS prevention and call for longitudinal studies to confirm these results and develop tailored dietary strategies.